An antimicrobial stewardship intervention on antibiotic prophylaxis for transrectal prostate biopsies in a veteran population - Jessica Bennett; Tenley Ryan; Jane Eason; Neena Thomas-Gosain (Antimicrobial Stewardship & Healthcare Epidemiology)
This retrospective review describes changes in prophylactic antibiotic prescribing practices for Veterans undergoing transrectal ultrasound-guided prostate biopsy (TRUPB) and the incidence of post TRUPB infection-related hospitalizations before and after an antimicrobial stewardship intervention.